Determinants and Consequences of Perceived Risks among Foreign Medical Tourists in Pakistan: An Empirical Investigation - Mehboob Ahmad; Adnan Ahmed Sheikh (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study aims to examine the factors that impact individuals' Behavioural Intentions towards Medical Health Tourism (BIMT) in Pakistan, focusing specifically on the evaluation of protection motivation appraisals (Coping Appraisal and Threat Appraisal). The protection motivation theory and the Knowledge, Attitude, and Behavior (KAB) model are two foundational models for the major mediating variable which is Perceived Risk in Medical Tourism (PRMT). The data from 238 foreign medical tourists, who were visiting certified Pakistani hospitals such as Agha Khan Karachi, Shifa International Islamabad, and Shaukat Khanam Pakistan, was analyzed using the Smart PLS-SEM (Partial Least Square Structural Equation Modeling) technique 3.0. These tourists were seeking treatment for a specific disease. The study results indicate that coping appraisal has no significant impact on PRMT. Nevertheless, the evaluation of potential threats did result in an elevation in perceived risk and threat, consequently influencing the conduct of those seeking medical treatment abroad. These findings are advantageous for administrators, practitioners, and scholars, as they contribute to a deeper comprehension of medical tourism in Pakistan and its advancement. This study had some limitations, which were subsequently addressed through the inclusion of recommendations for future research.